The Relationship Between Symptoms of Anxiety and Somatic Symptoms in Health Professionals During the Coronavirus Disease 2019 Pandemic - Li H (Dove Medical Press, 2020)
Hehua Li,1,* Yaping Zhang,2,3,* Honggang Wang,4 Jing Liang,4 Yongjie Zhou,2,3 Yuanyuan Huang,1 Tianyi Zhai,1 Qiong Yang,1 Mingzhe Yang,1 Yuping Ning,1,5 Hongbo He,1 Kai Wu,6 Fengjuan Chen,7 Fengchun Wu,1,5,8 Xiangyang Zhang1,9 1Department of Psychiatry, The Affiliated Brain Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Research Center for Psychological and Health Sciences, China University of Geosciences, Wuhan, People’s Republic of China; 3Affiliated Wuhan Mental Health Center, Tongji Medical College of Huazhong University of Science & Technology, Wuhan, People’s Republic of China; 4Qingdao Mental Health Center, Qingdao University, Qingdao, People’s Republic of China; 5The First School of Clinical Medicine, Southern Medical University, Guangzhou, People’s Republic of China; 6Department of Biomedical Engineering, School of Materials Science and Engineering, South China University of Technology (scUT), Guangzhou, People’s Republic of China; 7Department of Medical, Guangzhou Eighth People’s Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 8Guangdong Engineering Technology Research Center for Translational Medicine of Mental Disorders, Guangzhou, People’s Republic of China; 9CAS Key Laboratory of Mental Health, Institute of Psychology, Chinese Academy of Sciences, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fengchun WuInstitute of Psychology, The Affiliated Brain Hospital of Guangzhou Medical University, Liwan District, Guangzhou 510370, People’s Republic of ChinaEmail 13580380071@163.comXiangyang ZhangInstitute of Psychology, Chinese Academy of Sciences, Chaoyang District, Beijing 100101, People’s Republic of ChinaEmail zhangxy@psych.ac.cnBackground: The pandemic of coronavirus disease 2019 (COVID-19) has posed a threat to global health. Increasing studies have shown that the mental health status of health professionals is very poor during the COVID-19 epidemic. At present, the relationship between somatic symptoms and symptoms of anxiety of health professionals during the COVID-19 has not been reported. The purpose of this study was to explore the frequency of somatic symptoms and its related factors in health professionals with symptoms of anxiety during COVID-19 in China.Methods: A total of 606 health professionals were assessed online with the Chinese version of the 7-item Generalized Anxiety Disorder (GAD-7) scale, 7-item Insomnia Severity Index (ISI) and the somatization subscale of Symptom Checklist 90 (SCL-90).Results: The percentage of symptoms of anxiety, somatic symptoms and insomnia in all health professionals was 45.4%, 12.0%, and 32%, respectively. The frequency of somatic symptoms in health professionals with symptoms of anxiety was 22.9%. The SCL-90 somatization subscale score was significantly positively correlated with history of somatic diseases, GAD-7 score and ISI score in participants with symptoms of anxiety.Conclusion: During the COVID-19, symptoms of anxiety, insomnia, and somatic symptoms are commonly observed in health professionals. Insomnia and symptoms of anxiety are independently associated with somatic symptoms of health professionals with symptoms of anxiety.Keywords: somatic symptoms, coronavirus disease 2019, health professionals, frequency, related factors